Bibliometric Analysis of Author Productivity of Articles Related to Islamic Manuscripts in Indonesia - Afiyani, Aqilah Dzira; Alfariza, Rahma Devianti; Magfiroh, Mahlul; Puspita, Anindya Gita (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2025)
Background: Indonesia possesses a vast collection of 82,158 manuscripts, which hold valuable historical, cultural, and religious information. Among these, Islamic manuscripts play a significant role in the intellectual heritage of the region. However, the number of academic studies and publications related to these manuscripts remains limited compared to the total number owned. This indicates a gap between the availability of manuscript resources and scholarly attention towards them.Objective: This study aims to analyze the productivity and collaboration patterns of researchers who study Islamic manuscripts in Indonesia. By conducting a bibliometric analysis, the study seeks to identify the most productive authors, collaboration networks, and publication trends over the past decade. The ultimate goal is to motivate increased academic interest and research on Islamic manuscripts.Methods: This research employed bibliometric analysis to measure authorship productivity and collaboration using publication data from 2013 to 2023. Key indicators included the number of publications per author, author collaboration networks, and yearly publication trends. To test whether the distribution of author productivity aligns with Lotka’s Law, the Kolmogorov–Smirnov (K–S) test was used with a significance level of α = 0.05.Results: The analysis identified Jamaluddin as the most productive author in the field of Islamic manuscript studies, while Undang Ahmad Darsa was found to have the most extensive author collaboration network. The period between 2019 and 2023 marked the highest productivity, with 123 articles published. It was also found that 89% of the authors contributed only one article during the 2013–2023 period. The K–S test showed a Dmax value of 0.096, which is greater than the critical value of 0.08. Therefore, H0 is accepted and H1 is rejected, indicating that the productivity distribution does not conform to Lotka’s Law.Conclusion: This study reveals that research productivity in the field of Islamic manuscripts in Indonesia is concentrated among a few individuals, with most authors contributing only once. The findings highlight the need for broader scholarly engagement and collaboration in this area. Encouraging more researchers to study Islamic manuscripts is essential to preserving and understanding Indonesia’s rich manuscript heritage.